2016
DOI: 10.4172/2161-069x.1000413
|View full text |Cite
|
Sign up to set email alerts
|

Admission CRP Level as an Indicator for the Need of Percutaneous Cholecystostomy in Acute Cholecystitis

Abstract: Background: Percutaneous cholecystostomy (PC) and conservative treatment are alternatives to surgery in patients with moderate acute calculous cholecystitis. Failure or non-improvement after conservative treatment is an indication for PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…CRP is an acute-phase reactant produced by hepatocytes and may be elevated in many infectious, autoimmune, and cancerous diseases, including acute cholecystitis. [12] There are some studies in the literature that support our study and suggest that CRP may be an important predictive marker for CAC. Mahmood et al showed that a CRP value > 55 mg/L is an important marker for CAC.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…CRP is an acute-phase reactant produced by hepatocytes and may be elevated in many infectious, autoimmune, and cancerous diseases, including acute cholecystitis. [12] There are some studies in the literature that support our study and suggest that CRP may be an important predictive marker for CAC. Mahmood et al showed that a CRP value > 55 mg/L is an important marker for CAC.…”
Section: Discussionsupporting
confidence: 83%
“…Studies comprising scoring systems or predictive factors have been conducted to differentiate between CAC. [ 6 , 11 , 12 ] However, no studies in the literature have created an algorithm using the decision tree method. In this respect, our algorithm is the first in the literature.…”
Section: Discussionmentioning
confidence: 99%